2002
DOI: 10.1002/ajh.10101
|View full text |Cite
|
Sign up to set email alerts
|

Increased circulating activated endothelial cells, vascular endothelial growth factor, and tumor necrosis factor in thalassemia

Abstract: An increased number of circulating endothelial cells (CECs) was demonstrated in a-and b-thalassemic patients, b-thalassemia/hemoglobin E (BE), both splenectomized (BE [S]) and non-splenectomized (BE[NS]), had higher numbers of CECs than a-thalassemia, both HbH (a-thal l/a-thal 2; H) and HbH with hemoglobin Constant Spring (a-thal 1/CS; H/CS). CECs were also increased in heterozygous HbE (EA) and homozygous HbE (EE). The highest level of tumor necrosis factor-a (TNF-a) was found in HbH/CS patients, whereas the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
47
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 85 publications
(53 citation statements)
references
References 26 publications
4
47
0
1
Order By: Relevance
“…In this study, we found a negative correlation between L Retic and various erythropoietic inhibitory cytokines such as TNF-Ī±, IFN-Ī³, IL-10 and VEGF which may reflect the impaired reticulocytes maturation in these thalassemic patients. Recent studied reported that, in vivo IFN-Ī³ neutralization confirmed that IFN-Ī³ contributed to erythropoietic suppression but not reduced red blood cell survival [19] and VEGF which found to be increased in thalassemic patients [47,48] could modulate the hematopoietic system by suppression of BM-hematopoiesis, leading to activation of extramedullary hematopoiesis in the liver and spleen [49]. VEGF levels may be related to the clinical severity of thalassemia intermedia, as expressed by the degree of hepatomegaly and splenectomy [50].…”
Section: Parametersmentioning
confidence: 94%
“…In this study, we found a negative correlation between L Retic and various erythropoietic inhibitory cytokines such as TNF-Ī±, IFN-Ī³, IL-10 and VEGF which may reflect the impaired reticulocytes maturation in these thalassemic patients. Recent studied reported that, in vivo IFN-Ī³ neutralization confirmed that IFN-Ī³ contributed to erythropoietic suppression but not reduced red blood cell survival [19] and VEGF which found to be increased in thalassemic patients [47,48] could modulate the hematopoietic system by suppression of BM-hematopoiesis, leading to activation of extramedullary hematopoiesis in the liver and spleen [49]. VEGF levels may be related to the clinical severity of thalassemia intermedia, as expressed by the degree of hepatomegaly and splenectomy [50].…”
Section: Parametersmentioning
confidence: 94%
“…4) (Sonakul et al 1980). Thromboembolism in HbE b thalassemia seems to involve platelets, a reactive thalassemic red cell surface, coagulation factors, and abnormal endothelium (Butthep et al 2002;Pattanapanyasat et al 2004). …”
Section: Thromboembolismmentioning
confidence: 99%
“…Since these hemorheological impairments are thought to increase blood flow resistance in microvessels, they could accelerate endothelial dysfunction and vascular injury (40,41). Soluble adhesion molecules and vascular adhesion phenomena are potential markers of this endothelial activation (5,23). In SCA patients, a combination of the trapping of nondeformable cells and the interactions between sickle reticulocytes, leukocytes, and endothelial cells delay the transit time of RBCs through the capillaries and contribute to the initiation and progression of vasoocclusive crises (3,16,19,23).…”
mentioning
confidence: 99%